Identification of interleukin-6 as an autocrine growth factor for Epstein-Barr virus-immortalized B cells. - Tosato, G (1990)
Autocrine growth factors are believed to be important for maintenance of an immortalized state by Epstein-Barr virus (EBV), because cell-free supernatants of EBV-immortalized cell lines promote the proliferation of autologous cells and permit their growth at low cell density. In this study, we provide evidence for the existence of two autocrine growth factor activities produced by EBV-immortalized lines distinguished by size and biological activities. Much of the autocrine growth factor activity in lymphoblastoid cell line supernatants resided in a low-molecular-weight (less than 5,000) fraction. However, up to 20 to 30% of the autocrine growth factor activity resided in the high-molecular-weight (greater than 5,000) fraction. While the nature of the low-molecular-weight growth factor activity remains undefined, the high-molecular-weight growth factor activity was identified as interleukin-6 (IL-6). Culture supernatants from six EBV-induced lymphoblastoid cell lines tested contained IL-6 activity, because they promoted proliferation in the IL-6-dependent hybridoma cell line B9. In addition, a rabbit antibody to human IL-6 neutralized the capacity of the high-molecular-weight (greater than 5,000) fraction of a lymphoblastoid cell line supernatant to promote growth both in autologous EBV-immortalized cells and in B9 cells. Similarly, this high-molecular-weight autocrine growth factor activity was neutralized by a monoclonal antibody to human IL-6. Furthermore, characteristic bands, attributable to IL-6, were visualized in supernatants of each of four EBV-induced lymphoblastoid cell lines after immunoprecipitation with a rabbit antiserum to human IL-6. Thus, in addition to its previously reported properties, IL-6 is an autocrine growth factor for EBV-immortalized B cells cultured under serum-free conditions.